Hospital market concentration and the use of mechanical circulatory support devices in acute myocardial infarction complicated by cardiogenic shock - Adam S. Vohra; Sun-Joo Jang; Dmitriy N. Feldman; Parag Goyal; Udhay Krishnan; Christopher Sciria; Jim W. Cheung; Luke K. Kim (BMC, 2022)
Abstract Background As health care markets in the United States have become increasingly consolidated, the role of market concentration on physician treatment behavior remains unclear. In cardiology, specifically, there has been evolving treatment of acute myocardial infarction complicated by cardiogenic shock (AMI-CS) with increasing use of mechanical circulatory support (MCS). However, there remains wide variation in it use. The role of market concentration in the utilization of MCS in AMI-CS is unknown. We examined the use of MCS in AMI-CS and its effect on outcomes between competitive and concentrated markets. Methods and results We used the National Inpatient Sample to query patients admitted with AMI-CS between 2003 and 2009. The primary study outcome was the use of mechanical circulatory support. The primary study exposure was market concentration, measured using the Herfindahl-Hirschman Index, which was used to classify markets as unconcentrated (competitive), moderately concentrated, and highly concentrated. Baseline characteristics, procedures, and outcomes were compared for patients in differently concentrated markets. Multivariable logistic regression was used to examine the association between HHI and use of MCS. Results There were 32,406 hospitalizations for patients admitted with AMI-CS. Patients in unconcentrated markets were more likely to receive MCS than in highly concentrated markets (unconcentrated 46.8% [5087/10,873], moderately concentrated 44.9% [2933/6526], and high concentrated 44.5% [6676/15,007], p < 0.01). Multivariable regression showed that patients in more concentrated markets had decreased use of MCS in patients in later years of the study period (2009, OR 0.64, 95% CI 0.44-0.94, p = 0.02), with no effect in earlier years. There was no significant difference in in-hospital mortality. Conclusion Multivariable analysis did not show an association with market concentration and use of MCS in AMI-CS. However, subgroup analysis did show that competitive hospital markets were associated with more frequent use of MCS in AMI-CS as frequency of utilization increased over time. Further studies are needed to evaluate the effect of hospital market consolidation on the use of MCS and outcomes in AMI-CS.